Probabilistic analysis of soil consolidation via prefabricated vertical drains - Bari, Wasiul; Shahin, Mohamed; Nikraz, Hamid (American Society of Civil Engineers (ASCE), 2013)
Soil consolidation by prefabricated vertical drains (PVDs) relies on some soil properties that are spatially variable, such as the coefficient of permeability. However, the design of soil consolidation via PVDs has been traditionally carried out deterministically and thus can be misleading because of the ignorance of the uncertainty associated with the inherent spatial variation of soil properties. In this paper, the effects of spatial variability of soil permeability on soil consolidation by PVDs are investigated stochastically, and the corresponding uncertainty associated with the degree of consolidation is statistically quantified and analyzed.